Pemanfaatan Portal Online Bagi Mahasiswa (Studi Kasus Mahasisw KPI Universitas Islam Negeri Imam Bonjol Padang) - Rika Gusriani; Irta Sulastri; Yummil Hasan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
In general, online media is information that is presented online on the internet. Online media has a very wide scope, ranging from online TV, online radio, and online news portals. That an online news portal is a site or web page that contains the types of news. So a news portal is a site that displays information about information that occurs to the public. It can be seen that there are many news portals that have sprung up on the internet, making it easier for readers to get the latest information. Based on the observations that the author made that KPI students of the Faculty of Da'wah and Communication Sciences UNIVERSITAS  IB Padang in obtaining information by using or accessing information on news portals. That the news portals accessed by KPI students are detik.com, kompas.com, tribunnews, viva.co.id, okezone.com, Kapanlagi.com, online republic, realmberita.com, padangekspres.com, Suarakampus.com. Utilization of online news portals for KPI students as information, information about academics, job vacancies, tourism, technology and crime. The supporting factor is due to curiosity and adding insight along with being supported by cellphone (HP) facilities. The inhibiting factor is due to eye fatigue, inaccurate news, and typing errors in writing.